Prehabilitation in high-risk patients scheduled for major abdominal cancer surgery: a feasibility study - Waterland, Jamie L.; Ismail, Hilmy; Granger, Catherine L.; Patrick, Cameron; Denehy, Linda; Riedel, Bernhard; Beaumont, Anna; Bruns, Emma; Burbury, Kate; Carty, Danika; Chahal, Rani; Christelis, Georgina; et al. (Perioperative medicine (London), 2022)
Background Patients presenting for major surgery with low cardiorespiratory fitness (deconditioning) and other modifiable risk factors are at increased risk of postoperative complications. This study investigated the feasibility of delivering prehabilitation in high-risk patients scheduled for major abdominal cancer surgery. Methods Eligible patients in this single-center cohort study included patients with poor fitness (objectively assessed by cardiopulmonary exercise testing, CPET) scheduled for elective major abdominal cancer surgery. Patients were recruited to participate in a prehabilitation program that spanned up to 6 weeks pre-operatively and comprised aerobic and resistance exercise training, breathing exercise, and nutritional support. The primary outcome assessed pre-specified feasibility targets: recruitment >70%, retention >85%, and intervention adherence >70%. Secondary outcomes were assessed for improved pre-operative functional status and health-related quality of life and for postoperative complications. Results Eighty-two (34%) out of 238 patients screened between April 2018 and December 2019 were eligible for recruitment. Fifty (61%) patients (52% males) with a median age of 71 (IQR, 63-77) years participated in the study. Baseline oxygen consumption the at anaerobic threshold and at peak exercise (mean[+ or -]SD: 9.8[+ or -]1.8 and 14.0[+ or -]2.9 mL/kg/min, respectively) confirmed the deconditioned state of the study cohort. The retention rate within the prehabilitation program was 84%, with 42 participants returning for repeat CPET testing. While >60% of participants preferred to do home-based prehabilitation, adherence to the intervention was low--with only 12 (28%) and 15 (35%) of patients having self-reported compliance >70% with their exercise prescriptions. Conclusion Our prehabilitation program in high-risk cancer surgery patients did not achieve pre-specified targets for recruitment, retention, and self-reported program adherence. These findings underpin the importance of implementation research and strategies for the prehabilitation programs in major surgery. Trial registration Australian New Zealand Clinical Trials Registry (ACTRN12620000073909) retrospectively registered. Keywords: High-risk patients, Major surgery, Cardiopulmonary exercise testing, CPET, Prehabilitation